Análisis financiero en la empresa Profermaco Cia. Ltda., de la ciudad de Quito, en el periodo 2014-2015 - Santander Proaño, Fernando Moisés (2017)
The present research is a determinant source of information, because it allows to know how the business is visualized in the near future and the importance of the current decision making, which have an impact in the present and in the near future. The execution of the financial analysis allowed the objectives set out in the thesis project to be fulfilled, which were aimed at applying a horizontal analysis in order to know the changes suffered by the accounts, either increase or decrease from one period to another, the application of the vertical analysis that analyzes the behavior of the accounts in a determined period; as well as the realization of the different types of financial indicators specific to the company's commercial activity; in the same way with the results achieved a Financial Report that is directed to the Manager of the company as it will be of valuable assistance for the use of its resources, in the decision making and good progress of the business. In conclusion, the financial structure of the company presents an adequate conformation, except in certain items such as sales that must be kept in growth to achieve an adequate profitability within the income, through the application of each one of the indicators was able to know the liquidity , indebtedness and profitability maintained by the company in the same period that allows it to take advantage of its resources in an efficient way and thus determine the best strategies to generate productivity with the liquidity of the company.